7 Archives of Marland 61-52 - (:unkn) unknown (My University, 1678)
"Forasmuch as there is nothing more acceptable to almighty God then the true and Sincere Service & worship of him according to his holy will & fforasmuch as the Sanctifying or keepeing Holy of the Lords day comonly called Sunday is and hath been esteemed by the present & all primitive Christian Churches & people a principall and cheife part of the said Worship, which day in most places in this Province hath been & still is profaned and neglected by a wicked and disorderly sort of people by working Drunkeness swearing gameing vnlawfull pastimes and other Debaucheries to the high dishonnor of almighty God the Scandall of Christian Religion... That noe person or persons from & after the time aforesaid shall profane or abuse the said Lords day as aforesaid by Drunkeness Swearing gameing at Cards Dice Billiards Shuffell boards bowles Nynepins horserace fowling or hunting or any other vnlawfull Sportes or recreations "
Keywords: SABBATH-BREAKING LAW